The Contribution of Parenting Styles in Building Early Childhood’s Character at Al Ikhlas Konggo Kindergarten - Nofianti, Rita; Hadi Saputra Panggabean; Almanah Rambe (JOLADU: Journal of Language Education, 2024)
Numerous scientific disciplines have focused a great deal of study attention on parenting. The way a parent interacts with their child in various circumstances is reflected in their parenting style. The range of parenting styles includes authoritative, permissive, authoritarian, and neglectful approaches, and each has a unique effect on the social, emotional, and cognitive development of a child. This study tried to prove how parenting styles can either promote emotional intelligence, resilience, and self-worth, or they can cause behavioral problems, psychological discomfort, and a decline in social functioning. This research employed a qualitative descriptive approach. It was done in Al Ikhlas Konggo kindergarten with documentation, interviews, and observation as data collection technique. This study employed the three-pronged approach to data analysis proposed by Miles and Huberman. This research results found that parenting style in shaping the character of early childhood based on the value of politeness and courtesy has mostly been done well, namely by giving direction, advice, and giving good examples to children so that they always behave well so that someday children will become human beings with Islamic character. In addition, what dominates the parenting styles of parents whose children attend Al-Ikhlas Konggo Kindergarten is democratic parenting.